2006
DOI: 10.1143/jjap.45.4018
|View full text |Cite
|
Sign up to set email alerts
|

Ammonothermal Epitaxy of Thick GaN Film Using NH4Cl Mineralizer

Abstract: Single-crystalline GaN films of ≤ 110 µm in thickness have been fabricated on hydride vapor phase-grown (0001) GaN substrates by employing a relatively low-pressure (≤170 MPa) ammonothermal growth method with NH4Cl as mineralizer. Metallic Ga and polycrystalline GaN has been the chosen precursor. An average growth speed on the (0001) face of the substrate of ≥5 µm/day was observed when using metallic Ga and about 7 µm/day for GaN. The maximum growth speed of 27.5 µm/day was achieved for the film grown at a sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 12 publications
(13 reference statements)
1
73
0
Order By: Relevance
“…Our approach is on the acidic mineralizers since relatively low temperature (o550 1C) and pressure (o150 MPa) can be applied [4]. Moreover, the solubility is of regular type which allows one to work with a positive temperature gradient in the growth vessel or simply use a controlled cooling down to establish the supersaturation necessary to trigger nucleation of the growth species [4].…”
Section: Introductionmentioning
confidence: 99%
“…Our approach is on the acidic mineralizers since relatively low temperature (o550 1C) and pressure (o150 MPa) can be applied [4]. Moreover, the solubility is of regular type which allows one to work with a positive temperature gradient in the growth vessel or simply use a controlled cooling down to establish the supersaturation necessary to trigger nucleation of the growth species [4].…”
Section: Introductionmentioning
confidence: 99%
“…A detailed description on the experimental routine has already been given elsewhere [4,6]. An autoclave with a Pt inner liner to prevent from corrosion was used for the growth.…”
Section: Methodsmentioning
confidence: 99%
“…Basic mineralizers were reported to obtain single-phase hexagonal GaN [1], which is used by some groups [1][2][3]. We reported already that the handling of acidic mineralizer is relatively simple and that growth can be performed under considerably lower pressure and temperature [4,5]. A study on the effect of the acidic mineralizer on GaN growth performance supports the use of acidic mineralizers and the growth yield can be tuned upon modifying the acidity [6].…”
Section: Introductionmentioning
confidence: 93%
“…After these pioneering works of microcrystalline GaN synthesis, the research started to focus on seeded growth of GaN via fluid transport (Callahan et al, 2004). Retrograde solubility of GaN in ammono-basic solution was reported in a technical journal in 2005 (Hashimoto et al, 2005) as well as in a patent application (Dwiliński et al, 2001), while research on ammono-acidic conditions revealed normal dependence of solubility on temperature (Kagamitani et al, 2006). In 2007, the main focus of the ammonothermal GaN growth has shifted from thick-film growth to bulk growth (Hashimoto et al, 2007) and an exceptionally high-quality GaN bulk crystal was demonstrated in 2008 (Dwiliński et al, 2008).…”
Section: Development History and Current Activities Of The Ammonothermentioning
confidence: 99%
“…Although Ni-Cr superalloy presents excellent corrosion resistance against water and salt water, it is seriously corroded when exposed to acidic supercritical ammonia. To avoid corrosion of the autoclave, the acidic ammonothermal method employs Pt-based liner (Kagamitani et al, 2006). In addition to extreme cost of the liner, it is quite challenging to cover all wet surfaces of high-pressure components such as valves, safety rupture discs, and pressure transducers.…”
Section: The Impact Of Acidity On the Autoclave Materialsmentioning
confidence: 99%